Choice of Treatment Plan Based on Root Canal Therapy versus Extraction and Implant Placement: A Mini-Review - Parirokh, Masoud; Zarifian, Ahmadreza; Ghoddusi, Jamileh (Iranian Endodontic Journal, 2015)
Case selection and treatment plan are important aspects of endodontic treatment. Dentists should organize the treatment plan based on their knowledge, abilities, skills and more importantly the patients’ preference and dentition. Indubitably, the treatment plan for each patient is exclusive and “tailor-made” and cannot be used for all patients. Dentists’ self-estimation of their abilities opens up treatment options; however, in difficult or complicated cases it is advisable to refer to a specialist. Currently, one of the most challenging aspects in dentistry is the choice between extraction and placement of implant (EPI) instead of a complicated root canal treatment (RCT). Overemphasis on one treatment plan while neglecting other options, not only mislead the dentist but also impose unnecessary charges to the patients. This mini-review compares RCT to EPI from various aspects to help practitioners in routine decision making. Keywords: Case Selection; Dental Implant; Extraction; Implant; Root Canal Treatment; Tooth Replacement; Treatment Plan